A Systematic Review of SCRUM in Software Development - Eduard Pangestu Wonohardjo; Rizky Febriyanto Sunaryo; Yusuf Sudiyono (Politeknik Negeri Padang, 2019)
Scrum is a part of agile software development which also called incremental software development model. Scrum methodology commonly used to overcome uncertain condition and tight deadline. Scrum consists of three roles, they are product owner, development team, and scrum master. Scrum can be implemented on many areas such as development of education mobile application, integration of document management system, strengthen IT development centers, and many others. The successful of Scrum implementation depends on the skill and knowledge of the team members. The Scrum also has several risk factors and therefore needs risk management approaches. A comparison between agile and waterfall model is also discussed. The Scrum performance can also be tested with certain ways. Scrum used to make sure that all parts of the software can be delivered on time. The other benefits, scrum can make creative and productive workplace, and scrum can also increase business value.